Compressed temporalities within the musical- poetic: different variations of representation of the Homeric Hades localization - Souza, Marcelo Miguel de (Romanitas - Revista de Estudos Grecolatinos, 2013)
This article aims address the different variations of representations and locations of Homeric Hades. Raising issues related to the world of the dead Greek and representations contained in Iliad and Odyssey. For this, we use an approach that considers oral-musical compositions of the poems, and also the influences the composition within the texts we have.